HAKIKAT MANUSIA DAN IMPLIKASINYA DALAM PROSES PENDIDIKAN (Tinjauan Filsafat Pendidikan Islam) - Abdul Khobir (IAIN Pekalongan, 2010)
The essence of man in the perspective of Islamic EducationPhilosophy is something very important and fundamental that candetermine humans life. Searching about the essence of human naturecan not be only absorbed in the thinking about the basic elements thatdetermine the human, such as aspects of physical and spiritual aspectswhich include: passion, reason, qalb and spirit. But the basic elementsthat exist in human beings are the foundation when we are going tounderstand human nature. By basing on an understanding of humannature, activities and educational process is run and aims to be ableto develop the human personality. The ultimate goal of education ispersonal excellence based on the principle of self-realization, ie torealize the potential that already exists in human beings in the form ofmoral potential, skills and physical development.